The Level of Students’ Metacognitive Reading Strategy Awareness - Yulvita Christanti Pelaro; Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2022)
The objective of the research is to find out the level of students’ metacognitive reading strategy awareness in English language study Program of Sintuwu Maroso Poso. The type of the research is quantitative research. The role of the researcher was the observer. The location of the research in Teacher and Education Faculty of Sintuwu Maroso University on Jalan P. Timor No. 1 Poso. The Source of the research all of the fifth and seventh semester students at English Department of Sintuwu Maroso University consist of 30 students. The technique of data collection used is questionnaire. The questioner adopted from Mochtari and Reicahrd (2002). The questionnaire sent to the students in Google form. The finding of the research obtained that the level of students’ metacognitive reading strategy awareness is high with the mean score of 3,7. The score means that the students usually uses the metacognitive strategy when reading the English text. The Metacognitive strategy Awareness consist of three strategy namely Global strategy, supporting strategy and problem solving strategy